EXPERT ANALYSIS OF THE VERSION OF THE INVOLVEMENT OF ELECTROSTATIC DISCHARGE WITH PACKAGES OF CARDBOARD TO FIRE - I. Taubkin (Теория и практика судебной экспертизы)
On the example of one section of the show features forensic expert analysis version ofthe involvement of electrostatic discharge packs of cardboard in a "re truck. The materialis a handbook for experts, to assess the risk of electrostatic discharge from the surfaceof the sheet of dielectric materials.